Program bimbingan dan konseling untuk mengatasi kesulitan belajar siswa SD Negeri 05 Ciganjur Jakarta Selatan - Solihatun Solihatun; Sisca Folastri (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2019)
The study was conducted at SDN 05 Ciganjur to produce a guidance and counseling program in overcoming student learning difficulties. The method used is descriptive quantitative approach. The PTSDL AUM calculation was used in this study. The overall score of achievements of the respondents are in the sufficient category. Being in good quality, namely the sub-variable learning skills by 77.24%, the personal sub-variable by 79.31%, and the socio-emotional environment sub-variable by 85.71%. The implications of the results of this study can be input for classroom teachers, the government in an effort to help students with learning difficulties for the BK program at school